The Scar-in-a-Jar: studying potential anti?brotic compounds from the epigenetic to extracellular level in a single well - Chen, C.; Peng, Y.; Wang, Z.; Fish, P.; Kaar, J.; Koepsel, R.; Russell, A.; Lareu, Ricardo; Raghunath, M. (Stockton Press, 2009)
Background and purpose: Fibrosis, a pathological accumulation of collagen in tissues, represents a major global disease burden. Effective characterization of potential antifibrotic drugs has been constrained by poor formation of the extracellular matrix in vitro, due to tardy procollagen processing by collagen C-proteinase/BMP-1, and difficulties in relating this matrix to cell numbers in experimental samples. Experimental approach: The Scar-in-a-Jar model provided, in vitro, the complete biosynthetic cascade of collagen matrix formation including complete conversion of procollagen by C-proteinase/BMP-1, its subsequent extracellular deposition and lysyl oxidase-mediated cross-linking, achieved by applying the biophysical principle of macromolecular ‘crowding’. Collagen matrix deposition, velocity and morphology can be controlled using negatively charged ‘crowders’ in a rapid (2 days) mode or a mixture of neutral ‘crowders’ in an accelerated (6 days) mode. Combined with quantitative optical bioimaging, this novel system allows for in situ assessment of the area of deposited collagen(s) per cell. Key results: Optical evaluation of known and novel antifibrotic compounds effective at the epigenetic, post-transcriptional/translational/secretional level correlated excellently with corresponding biochemical analyses.Focusing on quantitation of deposited collagen, the Scar-in-a-Jar was most effective in assessing novel inhibitors that may have multiple targets, such as microRNA29c, found to be a promising antifibrotic agent. Conclusions and implications: This novel screening system supersedes current in vitro fibroplasia models, as a fast, quantitative and non-destructive technique. This method distinguishes a reduction in collagen I deposition, excluding collagen cross-linking, and allows full evaluation of inhibitors of C-proteinase/BMP-1 and other matrix metalloproteinases.